2020
DOI: 10.1021/acsami.0c16098
|View full text |Cite
|
Sign up to set email alerts
|

Mitrofanovite, Layered Platinum Telluride, for Active Hydrogen Evolution

Abstract: Two-dimensional (2D) layered catalysts have been considered as a class of ideal catalysts for hydrogen evolution reaction (HER) because of their abundant active sites with almost zero Gibbs energy change for hydrogen adsorption. Despite the promising performance, the design of stable and economic electrochemical catalyst based on 2D materials remains to be resolved for industrial-scale hydrogen production. Here, we report layered platinum tellurides, mitrofanovite Pt3Te4, which serves as an efficient and stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…When the current density reaches 10 mA cm –2 , the HER overpotentials for Pt 3 T 4 is only 46 mV, which is very close to than that of Pt electrode. A similar value was also reported for Pt 3 Te 4 nanocrystals, 28 in spite of the reduced surface-to-volume ratio in bulk compared to nanocrystals in ref ( 28 ). Moreover, all the Pt 3 T 4 samples (both pristine one and those ones modified by electrochemical treatments) show almost identical catalytic behavior at the low overpotential region.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…When the current density reaches 10 mA cm –2 , the HER overpotentials for Pt 3 T 4 is only 46 mV, which is very close to than that of Pt electrode. A similar value was also reported for Pt 3 Te 4 nanocrystals, 28 in spite of the reduced surface-to-volume ratio in bulk compared to nanocrystals in ref ( 28 ). Moreover, all the Pt 3 T 4 samples (both pristine one and those ones modified by electrochemical treatments) show almost identical catalytic behavior at the low overpotential region.…”
supporting
confidence: 87%
“… 27 Very recently, Bae et al have reported the synthesis of mitrofanovite Pt 3 Te 4 nanocrystals on a metallic molybdenum ditelluride (MoTe 2 ) template by an electrochemical method, which shows good HER performance. 28 However, the relationship between the HER activity and the physicochemical properties of Pt 3 Te 4 remains ambiguous, also considering the improper analysis of electronic band structure, with subsequent misleading theoretical model (see Section S16 in the Supporting Information for more details). Furthermore, such synthesis procedure is unsuitable for large-scale production and fails in reproducibility, due to its complexity.…”
mentioning
confidence: 99%
“…Moreover, the Te termination evolved into a nanometric oxide layer, whose thickness was estimated by quantitative XPS. Conversely, in the case of the Pt 3 Te 4 -nanocrystal, tellurium–oxide was always present [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, from the inspection of Figure 6 b it is evident that the Tafel slope of Pt 3 Te 4 decreases with the dimensionality. In fact, in the case of Pt 3 Te 4 nanocrystals, the reported Tafel slope was 33 mV/dec and the reported current density was as high as 7000 mA/cm 2 , which should be attributed to the formation of numerous edges and defects in the growth process and the consequent near-zero Gibbs free-energy change of hydrogen adsorption [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation